2020
DOI: 10.1007/s11845-020-02352-x
|View full text |Cite
|
Sign up to set email alerts
|

Urological service provision during the COVID-19 period: the experience from an Irish tertiary centre

Abstract: Purpose Urological service provision has changed dramatically with the advent of the SARS-CoV-2, necessitating restructuring and reorganization. The aim of this study was to review the reorganization of our unit, map the change in volume of departmental activities and discuss potential solutions. Methods Departmental activities over the months of April and May 2020 and 2019 were analysed. Details of admissions, operations, diagnostic procedures, outpatient reviews, morbidities and mortalities were recorded. Op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 7 publications
(7 reference statements)
1
18
0
Order By: Relevance
“…Moreover, the large decrease in number of surgeries for “non-urgent” cancer may have been due to the outbalance of high risk of new contagions compared with the risk of cancer progression in many cases. Similar results were reported by various cancer centres where surgeries were cancelled or postponed for months [ 24 , 28 ]. However, after the first wave of the pandemic, the number of cancer surgeries began to rise gradually [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, the large decrease in number of surgeries for “non-urgent” cancer may have been due to the outbalance of high risk of new contagions compared with the risk of cancer progression in many cases. Similar results were reported by various cancer centres where surgeries were cancelled or postponed for months [ 24 , 28 ]. However, after the first wave of the pandemic, the number of cancer surgeries began to rise gradually [ 29 ].…”
Section: Discussionsupporting
confidence: 88%
“…In the UK, cancer services and especially aggressive tumour types were given high priority to continue their activity (i.e., thoracic, H&N, and upper GI) [ 24 ]. In our SELCA population, overall, oncological surgery had a decline of 34% ( n = 1553 vs. 2336) in 2020 compared with 2019.…”
Section: Discussionmentioning
confidence: 99%
“…This large-scale surveillance system was informative for high-risk patients as they could make the decision to shield themselves if residing in a high-risk area. 43 The benefits of tracking were also evident in a study conducted by Ning et al who reported that active tracking reduced adverse effects that can occur from treatment delay and workforce incapacitation 46 (2) Outreach and Communication One of the most prominent strategies to ensure the maintenance of care continuity was regular communication between 77 P Brody et al 38 P P Butler et al 19 P P P P P P Casella et al 11 P P P P P P Chiang et al 14 P P P P P P Cinelli et al 53 P P Civantos et al 9 P P Civantos et al 49 P P P Collins et al 17 P P P P Curigliano et al 55 P P P Czernin et al 36 P P P P P de Marinis et al 39 P P P P Dharmarajan et al 51 P Elkaddoum et al 59 P P P Elkin et al 31 P Flannigan et al 57 P P Fosker 26 P P Frey et al 66 P Giuliani et al 58 P Gupta et al 48 P P P Grenda et al 54 P P Guven et al 12 P P P P Harky et al 61 P P P Indini et al 33 P P P P P P Jiang et al 60 P P Lee et al 15 P P P P P Lee et al 27 P P Lee et al 47 P P P Lobascio et al 56 P P Lombe et al 68 P P P Mei et al 21 P P P P P P Mendoza et al 23 P P P Millar et al 65 P Mirnezami et al 73 P P Morrison et al 69 P P Moss et al 32 P Mulvey et al 62 P...…”
Section: Covid-19 Andmentioning
confidence: 99%
“…19 Videoconferencing was also frequently utilized between healthcare staff and multidisciplinary teams in order to streamline healthcare provision, continue staff training and maintain timely diagnosis and treatment. 7,11,17,19,30,33,35,36,40,41,45,49,51 Silvestris et al 35 P P P P P Tagliamento et al 25 P P Tan et al 7 P P P P P Tey et al 10 P P P P Valenza et al 37 P P P P Van de Haar et al 3 P P P P P van der Lee et al 64 P Vanderpuye et al 40 P P P P P Wahed et a 28 P P P Wang et al 34 P P P P P Wakefield et al 20 P P P P Wei et al 71 P Weisel et al 8 P P P P P Wilkinson 42 P P P P P Wilson 30 P P P P P Wu et al 44 P P P P Yusuf 13 P P P P P Agyapong et al 52 Report Canada 1. Trailed providing self-subscribed supportive message to reduce anxiety and depression in cancer patients Ardizzone et al 75 Report USA 1.…”
Section: Covid-19 Andmentioning
confidence: 99%
See 1 more Smart Citation